Deposition law of flat fan nozzle for pesticide application in horticultural plants - Wu, Xiaoyi; Jia, Yalan; Luo, Bo; Chen, Chongchong; Wang, Yaxiong; Kang, Feng; Li, Jiale (International Journal of Agricultural and Biological Engineering, 2022)
Pesticide spraying is to protect the plants with adequate target coverage and a minimum of off-target drift. Understanding the spatial distribution characteristics of spray droplets is essential for regulating pesticide deposition, in order to investigate the relationship between the two at the mechanistic level and provide an accurate basis for nozzle selection, this study compared the characteristics of the atomization field under different pressures, angles, and flow rate types by phase Doppler particle analyzer (PDPA), the unit spatial density of droplet was used as a link to explore the internal mechanism that affects the deposition efficiency by constructing a transport model and conducting actual spraying experiments. The results showed that the cumulative distribution of droplet diameter could be perfectly fitted by the Rosin-Rammler correlation, and the deposition efficiency had a strong correlation with the peak particle size range. For strawberry and chrysanthemum plants, the optimal droplet deposition particle size ranges were 250-270 μm and 240-260 μm, respectively. This article explained the deposition efficiency from a single droplet dynamics mechanism and deposition of droplet cloud, which provided a new research idea for the study of precision plant protection. Keywords: pesticide transport, deposition, atomization field, PDPA DOI: 10.25165/j.ijabe.20221504.7502 Citation: Wu X Y, Jia Y L, Luo B, Chen C C, Wang Y X, Kang F, et al. Deposition law of flat fan nozzle for pesticide application in horticultural plants. Int J Agric & Biol Eng, 2022; 15(4): 27–38.